Keep the thread up! From humour to poetry. Silence as a spur to read and speak - Jean Perrot (Universidad de Zaragoza, 2021)
The purpose of this article is to proceed with a semiotic examination of several wordless picturebooks focussed on the use of a thread, Considering that it is the visual image which first and foremost prompts the meaning in iconotexts, we shall deal with it more particularly through the examination of two French picturebooks: the first one by Robert Scouvart, Histoire d'un fil (The Story of a Thread, Magnard 1990) shows how a single thread can magically delineate different characters introduced in an alluring play on words. The book will offer a distanced staging of the reading process through a humorous use of stereotypes close to those resorted to in comic strips. In the second part of my presentation we shall deal with Boutique Tic Tic, (Shop Pop Pop) by Frédéric Clément, (Albin Michel Jeunesse, 2018) a poetical description introduced under the aesthetic spell of Lewis Carrol's The Adventures of Alice in Wonderland, as suggested by the image of the white rabbit winking from a globe on the cover page. The book in the end will tell how a magical thread can unexpectedly and poetically have a « golden voice » during « a long minute of silence of Big Ben »... An original achievement fully illustrating Sandra Becket's declaration that « the 'interactive' and 'cinematic' qualities of similar productions [...] make them books for the 'digital age.' (2012, p. 99) Keywords: the magic thread, album without words, Histoire d'un fil, Boutique Tic Tic, humour, poetry.